Resenha de: The black legend in England - Meihy, José Carlos Sebe Bom (Revista de História, 1972)
MALTBY (Willian S.) . — The black Legend in England: The development of anti-Spanish sentiment, 1558-1660. Duke University Press. 1971, 180 pp.